EXPLORATION OF JELAMI TECHNIQUES USING NATURAL DYES OF TINGI WOOD (CERIOPS TAGAL) AND JASMINE (JASMINUM SAMBAC) IN ATBM SILK WEAVING FABRIC INTO ENVIRONMENTALLY FRIENDLY TEXTILES - Savitri, Savitri; Damayanti, Nuning Yanti; Sunarya, Yan Yan; Widiawati, Dian (Wimba : Jurnal Komunikasi Visual, 2025)
This paper discusses the results of research related to exploration and innovation in utilizing the potential of nature and environmentally friendly technology in creating textile motifs through the Jelami technique (Natural Footprint), which is a way of transferring traces of motifs and colors on fabric, using jasmine flowers as a motif builder and natural dyes of high wood as a form of color traces. This innovation is related to the rapid progress of Indonesia's textile industry, which is considered positive. Still, there are problems with environmental pollution caused by the increasing use of environmentally unfriendly materials, namely chemicals, which are very harmful to the ecosystem of human life and biodiversity. To address this issue, it is essential to anticipate potential problems by exploring alternatives in the textile industry's production process one alternative is research on the use of environmentally friendly materials. The method used is exploratory qualitative research. The initial stage is observation, literature study, and documentation, then the stage is determining jasmine flowers (Jasminum sambac) and natural dyes from high wood (Ceriobs candolleana) applied to ATBM silk fabrics through the jelami technique. The next stage is to experiment and explore the process of the jelami technique on fabrics to get a standard formulation to produce jasmine motifs that are consistent in shape and color. The stages of applying and designing motifs with jelami techniques use a craft creation approach (Gustami, 2006), namely the design, embodiment, and evaluation stages. Munsell's theory expresses color in three dimensions: taste, value and intensity. The result of the study is the novelty of jasmine motifs with natural dyes of high wood through the process of jelami techniques in the form of textiles to be applied to a variety of used objects that have high economic value and are environmental friendly